If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -6)(2.3x + -6) = 600 Reorder the terms: 3(-6 + x)(2.3x + -6) = 600 Reorder the terms: 3(-6 + x)(-6 + 2.3x) = 600 Multiply (-6 + x) * (-6 + 2.3x) 3(-6(-6 + 2.3x) + x(-6 + 2.3x)) = 600 3((-6 * -6 + 2.3x * -6) + x(-6 + 2.3x)) = 600 3((36 + -13.8x) + x(-6 + 2.3x)) = 600 3(36 + -13.8x + (-6 * x + 2.3x * x)) = 600 3(36 + -13.8x + (-6x + 2.3x2)) = 600 Combine like terms: -13.8x + -6x = -19.8x 3(36 + -19.8x + 2.3x2) = 600 (36 * 3 + -19.8x * 3 + 2.3x2 * 3) = 600 (108 + -59.4x + 6.9x2) = 600 Solving 108 + -59.4x + 6.9x2 = 600 Solving for variable 'x'. Reorder the terms: 108 + -600 + -59.4x + 6.9x2 = 600 + -600 Combine like terms: 108 + -600 = -492 -492 + -59.4x + 6.9x2 = 600 + -600 Combine like terms: 600 + -600 = 0 -492 + -59.4x + 6.9x2 = 0 Begin completing the square. Divide all terms by 6.9 the coefficient of the squared term: Divide each side by '6.9'. -71.30434783 + -8.608695652x + x2 = 0 Move the constant term to the right: Add '71.30434783' to each side of the equation. -71.30434783 + -8.608695652x + 71.30434783 + x2 = 0 + 71.30434783 Reorder the terms: -71.30434783 + 71.30434783 + -8.608695652x + x2 = 0 + 71.30434783 Combine like terms: -71.30434783 + 71.30434783 = 0.00000000 0.00000000 + -8.608695652x + x2 = 0 + 71.30434783 -8.608695652x + x2 = 0 + 71.30434783 Combine like terms: 0 + 71.30434783 = 71.30434783 -8.608695652x + x2 = 71.30434783 The x term is -8.608695652x. Take half its coefficient (-4.304347826). Square it (18.52741021) and add it to both sides. Add '18.52741021' to each side of the equation. -8.608695652x + 18.52741021 + x2 = 71.30434783 + 18.52741021 Reorder the terms: 18.52741021 + -8.608695652x + x2 = 71.30434783 + 18.52741021 Combine like terms: 71.30434783 + 18.52741021 = 89.83175804 18.52741021 + -8.608695652x + x2 = 89.83175804 Factor a perfect square on the left side: (x + -4.304347826)(x + -4.304347826) = 89.83175804 Calculate the square root of the right side: 9.477961703 Break this problem into two subproblems by setting (x + -4.304347826) equal to 9.477961703 and -9.477961703.Subproblem 1
x + -4.304347826 = 9.477961703 Simplifying x + -4.304347826 = 9.477961703 Reorder the terms: -4.304347826 + x = 9.477961703 Solving -4.304347826 + x = 9.477961703 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4.304347826' to each side of the equation. -4.304347826 + 4.304347826 + x = 9.477961703 + 4.304347826 Combine like terms: -4.304347826 + 4.304347826 = 0.000000000 0.000000000 + x = 9.477961703 + 4.304347826 x = 9.477961703 + 4.304347826 Combine like terms: 9.477961703 + 4.304347826 = 13.782309529 x = 13.782309529 Simplifying x = 13.782309529Subproblem 2
x + -4.304347826 = -9.477961703 Simplifying x + -4.304347826 = -9.477961703 Reorder the terms: -4.304347826 + x = -9.477961703 Solving -4.304347826 + x = -9.477961703 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4.304347826' to each side of the equation. -4.304347826 + 4.304347826 + x = -9.477961703 + 4.304347826 Combine like terms: -4.304347826 + 4.304347826 = 0.000000000 0.000000000 + x = -9.477961703 + 4.304347826 x = -9.477961703 + 4.304347826 Combine like terms: -9.477961703 + 4.304347826 = -5.173613877 x = -5.173613877 Simplifying x = -5.173613877Solution
The solution to the problem is based on the solutions from the subproblems. x = {13.782309529, -5.173613877}
| -4(5n+3)=20 | | -x^2-18x-18=0 | | 32y+7y^2=15 | | d-3=25 | | 5-5=13 | | 7x^2+3x+5=21 | | Lnx=3/4 | | 5/4=4x-2 | | 2x^2+3x-2=-1 | | 5/6x=4-11/12x | | 12x-22+9x-9=180 | | 3x^2+9x-24=-6 | | 7y-63/5=-3 | | 12x-22=9x-9 | | b=a/14 | | 8x^2+64x+16=8 | | -7x-8y=-49 | | 6x^2+12x-24=30 | | 12*4(x-7)=12*3(x+7) | | 1/3=2-2/9 | | 2c=(j+m) | | (5z-8)(4+z)=0 | | (x+4)x=480 | | 9x^2-36x-27=18 | | 12x^2+24x+24=48 | | s(t)=-16t^2+128t+5 | | x^2-12x+10=-1 | | -7u^2+30u-8=0 | | x^2+10x-7=4 | | 28-x/5=7/10 | | -5/2w-2/3=7/6w-2 | | 144=4t |